The Key to the Door? Teaching Awards in Australian Higher Education : Fellowship Final Report. - Israel, Mark (Australian Learning and Teaching Council (ALTC), 2011)
Final report of a Teaching Fellowship at the University of Western Australia. The research investigates the Australian teaching awards and their impact on awardees and their institutions. It considers the proposition that the higher education sector may have invested considerable effort in ensuring that excellent teachers get an award but paid little attention to what they may get out of an award. The researcher used a mixed method approach including review of program documentation, interviews with award winners and policy stakeholders, and an online survey of award recipients.